O nowych rozwinięciach nie-Marksowskiego materializmu historycznego - Greczko, Iwo (Człowiek i Społeczeństwo, 2025)
The subject of the review is a scientific monograph edited by Krzysztof Brzechczyn, entitled “New Developments in the Theory of Historical Process. Polish Contribution to Non-Marxian Historical Materialism” (Leiden, Boston: Brill, 2022) that collects application of non-Marxian Historical Materialism by Leszek Nowak and his followers. The author of the review draws special attention to the explanatory power of Nowak’s theory and the relevance of the predictions about the totalitarianization of capitalism, formulated by the Nowak several decades ago.